2007
DOI: 10.1100/tsw.2007.25
|View full text |Cite
|
Sign up to set email alerts
|

Acholeplasma laidlawiiPG8 Culture Adapted to Unfavorable Growth Conditions Shows an Expressed Phytopathogenicity

Abstract: Mycoplasmas are the smallest, self-replicating, prokaryotic organisms with avid biochemical potential and spreading in higher eukaryotes in nature. In this study, Acholeplasma laidlawii PG8 cells were cultivated on a deficient medium for 480 days resulting in a mycoplasma culture that was adapted in vitro to unfavorable growth conditions. Cells that survive this condition had decreased sizes (about 0.2 μm) and increased phytopathogenicity. This resulted in more frequent appearance of various morphological alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Acholeplasma is a widely distributed mycoplasma in nature and possesses very versatile adaptation capabilities [Chernov et al, 2005]. Among all its ecological capabilities, it is a causative agent of some plant diseases [Chernov et al, 2007[Chernov et al, , 2011. The successful virulence traits (infectivity, invasivity, toxigenicity and persistence) of Acholeplasma towards plants suggest that it can survive unfavorable conditions, such as oxidative stress, limited substrate and temperature fluctuations [Chernov et al, 2011].…”
Section: Potentially Phytopathogens In the Wormbed Leachatementioning
confidence: 99%
“…Acholeplasma is a widely distributed mycoplasma in nature and possesses very versatile adaptation capabilities [Chernov et al, 2005]. Among all its ecological capabilities, it is a causative agent of some plant diseases [Chernov et al, 2007[Chernov et al, , 2011. The successful virulence traits (infectivity, invasivity, toxigenicity and persistence) of Acholeplasma towards plants suggest that it can survive unfavorable conditions, such as oxidative stress, limited substrate and temperature fluctuations [Chernov et al, 2011].…”
Section: Potentially Phytopathogens In the Wormbed Leachatementioning
confidence: 99%
“…This might be in the case of A. laidlawii PG8. Earlier [1,5] we reported that starvation leadsA. laidlawii PG8 to dormancy.…”
Section: Resultsmentioning
confidence: 98%
“…About 700 protein spots were resolved in the analytic gel. Probably, the low resolution is connected with more broad pH range of IPG we used (3-10) then it is mainly used in the plant proteomic study (3)(4)(5)(6)(7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations